Colorectal cancer risk factors in patients with serrated polyposis syndrome: a large multicentre study. Issue 11 (11th August 2015) - Carballal, Sabela; Rodríguez-Alcalde, Daniel; Moreira, Leticia; Hernández, Luis; Rodríguez, Lorena; Rodríguez-Moranta, Francisco; Gonzalo, Victoria; Bujanda, Luis; Bessa, Xavier; Poves, Carmen; Cubiella, Joaquin; Castro, Inés; et al.
Abstract : Objective: Serrated polyposis syndrome (SPS) is associated with an increased colorectal cancer (CRC) risk, although the magnitude of the risk remains uncertain. Whereas intensive endoscopic surveillance for CRC prevention is advised, predictors that identify patients who have high CRC risk remain unknown. We performed a multicentre nationwide study aimed at describing the CRC risk in patients with SPS and identifying clinicopathological predictors independently associated with CRC. Design: From March 2013 through September 2014, patients with SPS were retrospectively recruited at 18 Spanish centres. Data were collected from medical, endoscopy and histopathology reports. Multivariate logistic regression was performed to identify CRC risk factors. Results: In 296 patients with SPS with a median follow-up time of 45 months (IQR 26–79.7), a median of 26 (IQR 18.2–40.7) serrated polyps and 3 (IQR 1–6) adenomas per patient were detected. Forty-seven patients (15.8%) developed CRC at a mean age of 53.9±12.8, and 4 out of 47 (8.5%) tumours were detected during surveillance (cumulative CRC incidence 1.9%). Patients with >2 sessile serrated adenomas/polyps (SSA/Ps) proximal to splenic flexure and ≥1 proximal SSA/P with high-grade dysplasia were independent CRC risk factors (incremental OR=2, 95% CI 1.22 to 3.24, p=0.006). Patients with no risk factors showed a 55% decrease in CRC risk (OR=0.45, 95% CI 0.24 to 0.86, p=0.01). Conclusions: Patients with SPS have an increased risk of CRC, although lower than previously published. Close colonoscopy surveillance in experienced centres show a low risk of developing CRC (1.9% in 5 years). Specific polyp features (SSA/P histology, proximal location and presence of high-grade dysplasia) should be used to guide clinical management.